A política de Ensino Médio Integrado no Instituto Federal Catarinense – Câmpus Avançado Sombrio: transformações e potencialidades - Espindola, Vanessa Dias (2023)
This research is linked to the Postgraduate Program in Education in Research Line 2: Educational Public Policies, pedagogical practices and their interfaces and to TransformAção: Study and Research Group on Public Policies and Pedagogical Work in Professional Education. The study aimed to analyze the transformations and potential of Integrated High School at the Câmpus Avançado Sombrio, of the Instituto Federal Catarinense, based on the implementation of the Integrated High School policy. To achieve this purpose, the research was based on three specific objectives: I) investigate the historicity of the Integrated High School policy and its movement at the Câmpus Avançado Sombrio, of the Instituto Federal Catarinense; II) understand the transformations that the EMI policy brought to professional and technological education at the IFC Advanced Shadow Campus; III) unveil the potential of the EMI policy in the Shadow Advanced Campus. The investigation presents a qualitative approach and is configured as a study and analysis from a dialectical perspective, based on the categories of historicity, contradiction and totality. As an instrument for data production, an electronic form was used in which 50 employees responded to the proposed questions. After the analysis, the interlocution group was also used. Theoretical references were studied on the policy of Technological Professional Education and on public educational policies and Integrated High School. There was also an analysis of the institution's internal documents and legislation. It was concluded that the transformations experienced by the research participants at the analyzed Institute and their perspectives on the EMI policy were fundamental to understanding the practical implementation of EMI on campus, the potential, as well as the weaknesses that employees encounter in its implementation. The implementation of the EMI policy caused significant educational changes, including integration, which presented itself as a power and, concomitantly, as a weakness of the EMI and also the main transformation regarding the policy. Therefore, the EMI, although it demonstrates weaknesses and challenges, its potential strengthens the possibility of implementing the EMI policy as the path to comprehensive training.